Agrobacterium tumefaciens-mediated transformation of drumstick (Moringa oleifera Lam.). Issue 6 (2nd November 2017) - Zhang, Junjie; Lin, Mengfei; Chen, Hanbin; Chen, Xiaoyang
ABSTRACT: Drumstick ( Moringa oleifera Lam.) is an industrially important tree species. Due to the availability of an efficient regeneration system, the present study was undertaken to develop a reliable and stable Agrobacterium tumefaciens -mediated transformation system for the genetic improvement of drumstick. A. tumefaciens strain EHA105, harbouring the plasmid pCAMBIA1301 containing the hygromycin phosphotransferase II and ß -glucuronidase genes driven by the CaMV 35S promoter, was used to establish a transformation system in drumstick. The use of vacuum infiltration-assisted Agrobacterium infection (excluding a pre-culture step) and co-cultivation for two days significantly increased the transformation frequency. Genomic integration and transgene expression were confirmed by β-glucuronidase (GUS) assays, polymerase chain reaction (PCR), Southern blot analysis and real-time quantitative PCR (RT-qPCR). This transformation protocol provides a basis for the future development of genetic engineering techniques to improve the performance of drumstick.